2018
DOI: 10.1371/journal.pone.0206376
|View full text |Cite
|
Sign up to set email alerts
|

The effects of oral contraceptive usage on thrombin generation and activated protein C resistance in Saudi women, with a possible impact of the body mass index

Abstract: Background and objectivesThe effect of oral contraceptive (OC) usage on coagulation has been studied worldwide. However, no such studies have been conducted in Saudi Arabia on Saudi women using OCs. The aim of this study was to investigate the effects of OC-induced changes of thrombin generation (TG) in the absence and presence of activated protein C (APC) or thrombomodulin (TM) in Saudi women.MethodsA total of 115 adult women, 47 on oral contraception (OC users) and 68 controls (not using OCs) were recruited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
4
8
0
Order By: Relevance
“…Oral contraceptives are well known to induce a significant procoagulant effect. Moreover, several authors showed a hypercoagulable thrombin generation profile after the addition of TM or activated protein C in this population 20,27‐29 . These findings were also observed in our subjects taking OC, with higher ETP and peak values following TM addition 26 .…”
Section: Discussionsupporting
confidence: 85%
“…Oral contraceptives are well known to induce a significant procoagulant effect. Moreover, several authors showed a hypercoagulable thrombin generation profile after the addition of TM or activated protein C in this population 20,27‐29 . These findings were also observed in our subjects taking OC, with higher ETP and peak values following TM addition 26 .…”
Section: Discussionsupporting
confidence: 85%
“…Numerous studies investigated the ETP‐based APC resistance, especially in the setting of hormonal contraceptive and hormone replacement therapies, reported as being responsible for an acquired APC resistance . Based on these studies, regulatory bodies recommends the assessment of the ETP‐based APC resistance during the development of novel steroid contraceptive agents .…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows the number of healthy donors per subgroup: men (49.6%), women without OCs (women -OCs, 37.6%) and women taking OCs (women + OCs, 12.8%). The mean age of the whole population was 35 ± 12 years (mean ± SD), and the median age was 30 years (IQR, [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The female group taking OCs was statistically younger than the men or women without OCs (P = .029 and P < .00, respectively).…”
Section: Study Population Characteristicsmentioning
confidence: 99%